Spondias mombin L. attenuates ventricular remodelling after myocardial infarction associated with oxidative stress and inflammatory modulation - Pereira, Bruna Letícia Buzati [UNESP]; Rodrigue, Alexane; Arruda, Fernanda Caroline de Oliveira [UNESP]; Bachiega, Tatiana Fernanda [UNESP]; Lourenço, Maria Angélica Martins [UNESP]; Corrêa, Camila Renata [UNESP]; Azevedo, Paula Schmidt [UNESP]; Polegato, Bertha Furlan [UNESP]; Okoshi, Katashi [UNESP]; Fernandes, Ana Angélica Henrique [UNESP]; de Paiva, Sergio Alberto Rupp [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP]; et al. (Wiley, 2020)
The objective of this study was to evaluate Spondias mombin L. (SM) pulp and its influence on cardiac remodelling after myocardial infarction (MI). Male Wistar rats were assigned to four groups: a sham group (animals underwent simulated surgery) that received standard chow (S; n = 20), an infarcted group that received standard chow (MI; n = 24), an infarcted group supplemented with 100 mg of SM/kg bodyweight/d, (MIS100; n = 23) and an infarcted group supplemented with 250 mg of SM/kg bodyweight/d (MIS250; n = 22). After 3 months of treatment, morphological, functional and biochemical analyses were performed. MI induced structural and functional changes in the left ventricle with worsening systolic and diastolic function, and SM supplementation at different doses did not influence these variables as analysed by echocardiography and an isolated heart study (P >.05). However, SM supplementation attenuated cardiac remodelling after MI, reducing fibrosis (P =.047) and hypertrophy (P =.006). Biomarkers of oxidative stress, inflammatory processes and energy metabolism were further investigated in the myocardial tissue. SM supplementation improved the efficiency of energy metabolism and decreased lipid hydroperoxide in the myocardium [group S (n = 8): 267.26 ± 20.7; group MI (n = 8): 330.14 ± 47.3; group MIS100 (n = 8): 313.8 ± 46.2; group MIS250: 294.3 ± 38.0 nmol/mg tissue; P =.032], as well as decreased the activation of the inflammatory pathway after MI. In conclusion, SM supplementation attenuated cardiac remodelling processes after MI. We also found that energy metabolism, oxidative stress and inflammation are associated with this effect. In addition, SM supplementation at the highest dose is more effective.
Keywords: myocardial infarction; oxidative stress; Spondias mombin; ventricular remodelling